Study on moths of the Herminia decipiens complex (Lepidoptera, Erebidae, Herminiinae) with descriptions of three new species - Owada, Mamoru; Wu, Shipher (Zootaxa, 2019)
Asian herminiine moths of the Herminia decipiens complex are revised and five allopatric species are recognized, i.e. Herminia decipiens (Hampson, 1898) in Nilgiri Hills, Khasi Hills, South China, Indochina, Malay Peninsula, H. terminalis (Wileman, 1915) in Taiwan, H. yuksam sp. nov. in East Nepal, Sikkim, H. borneo sp. nov. in Borneo and H. amamioshima sp. nov. in Amami-oshima Is., Shimo-Koshikijima Is. and South Kyushu (Kagoshima). Key to all species is given.